Application of ChatGPT in Improving Customer Sentiment Analysis for Businesses - Frans Sudirjo; Karno Diantoro; Jassim Ahmad Al-Gasawneh; Hizbul Khootimah Azzaakiyyah; Abu Muna Almaududi Ausat (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
In the contemporary era of digitization, prosperous enterprises exhibit a keen interest in the feedback and perceptions of their customers regarding the products or services they provide. The analysis of customer sentiment, which entails comprehending and construing customer emotions and viewpoints, has emerged as a crucial element of business tactics aimed at augmenting customer contentment and recognising avenues for enhancement. The objective of this study is to investigate and employ ChatGPT within the realm of business customer sentiment analysis. The central focus of this inquiry is predominantly qualitative in character. The procedure of gathering data entails careful scrutiny and systematic documentation of information, subsequently utilising analytical techniques such as data reduction, visualisation, and inference to deduce significant findings. The findings of the study indicate that the utilisation of ChatGPT has significant potential in enhancing the analysis of customer sentiment for commercial enterprises. This can aid in comprehending and addressing the requirements, inclinations, and contentment levels of customers. ChatGPT's proficiency in comprehending natural language, detecting customer emotions, and processing extensive data instantaneously, can furnish enterprises with valuable perspectives to enhance their decision-making processes.